The Effect of Pharmacological Preconditioning with Nicorandil before Elective Coronary Stenting on the Long-Term Prognosis of Patients with Stable Coronary Artery Disease - G. N. Soboleva; R. V. Gostishchev; A. N. Rogoza; T. I. Kotkina; A. N. Samko; Yu. A. Karpov (Столичная издательская компания, 2020)
Aim. To study nicorandil prescription effects before elective percutaneous coronary intervention (PCI) to prevent myocardial injury and 4a type acute myocardial infarction (MI, primary endpoint) and cardiovascular events (CVE) in the first year after PCI (secondary endpoint) in patients with stable coronary artery disease.Material and methods. 182 patients with stable coronary artery disease were included into the study and were randomized into two groups: nicorandil treatment group (n=90) and a control group with a standard medical treatment (n=92). Nicorandil was prescribed orally: 2 days before PCI - 30 mg/day; on the day of PCI - 20 mg 2 hours before intervention and 10 mg 6-12 hours after PCI; over the next 30 days - 30 mg/day. High sensitivity troponin I (hs-Tr) and creatine kinase-MB tests were carried out before PCI, 24 and 72 hours after the intervention; the 4a type MI was diagnosed according to the 4th Universal Definition. Non-fatal myocardial infarction, nonfatal stroke, death from cardiovascular diseases, repeat revascularization (PCI, coronary artery bypass surgery due to aggravation), hospital admissions for angina pectoris recurrence (without interventions) and death from any causes were considered as cardiovascular events. Data on adverse outcomes were collected over the hospital stay, and then 30, 180 and 365 days after the hospital discharge.Results. 4a type MI was diagnosed in 14 patients (8%), in women - 12% and in men - 6%. There was a significant decrease in the incidence of type 4a MI in the nicorandil group (n=3; 3%) compared with the control group (n=11; 12%; p=0.05). Secondary endpoint was recorded in 21% of patients. The relationship was found between 4a type MI and the incidence of CVE the next year after the PCI (p=0.01). In patients with type 4a MI CVE odd ratio increases 5.8 times with confidence interval from 1.5426 to 21.6024. According to the logistic regression analysis the significant relationship between hs-Tr growth 24 hours after the PCI and CVE incidence next year after the PCI was found with cutting value 389.8 pg/ml, AUC=0.641 (p=0.04).Сonclusion. Peroral nicorandil 30 mg/day 2 days before PCI, 20 mg 2 hours before surgery and 10 mg 6-12 hours after PCI, and 30 mg/day next 30 days after PCI decreases the risk of intraoperative myocardial injury and CVE in the next year after PCI.